2018
DOI: 10.1002/hep.29345
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome in women undergoing liver biopsy during pregnancy: A nationwide population‐based cohort study

Abstract: Apart from a moderately increased risk of preterm birth and small for gestational age, there was no association between liver biopsy during pregnancy and adverse pregnancy outcome; potential excess risks should be weighed against the advantages of having a liver biopsy that may influence clinical management of the patient and indirectly fetal health. (Hepatology 2017).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
(37 reference statements)
0
13
0
3
Order By: Relevance
“…23 In one small study, there was a small increased risk of premature birth, but no stillbirth was reported. 24 In some non-life-threatening clinical conditions, it may be reasonable to wait until delivery of the baby. Thus, the benefits of biopsy need to be balanced against the risks to the mother and baby.…”
Section: Pregnancymentioning
confidence: 99%
“…23 In one small study, there was a small increased risk of premature birth, but no stillbirth was reported. 24 In some non-life-threatening clinical conditions, it may be reasonable to wait until delivery of the baby. Thus, the benefits of biopsy need to be balanced against the risks to the mother and baby.…”
Section: Pregnancymentioning
confidence: 99%
“…Patient characteristics may differ from that of the general patient population, if histopathology report data are used to identify diseases that may otherwise not require biopsy, or where biopsy is typically carried out only for advanced disease. The ESPRESSO database is likely to have lower coverage for certain gastrointestinal diseases in patients where endoscopy102 and, eg, liver biopsy103 are sometimes avoided due to other concurrent conditions (eg, pregnancy). The new recommendations allowing for a non-biopsy celiac diagnosis in certain children,27 but not in adults,117 mean that not all children with incident celiac disease after 2012 may have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the ESPRESSO database includes information on procedures. Two recent papers failed to detect any substantial impact on pregnancy outcome from endoscopy or liver biopsy during pregnancy 102,103. Yet, pregnancy outcome may not only be seen as a consequence of parental gastrointestinal disease,101,104 ie, it could also be a risk factor for future gastrointestinal disease in the offspring 105107.…”
Section: Potential Research Use Of the Espresso Databasementioning
confidence: 99%
“…This study demonstrated no increased risk of bleeding or stillbirth. There was a moderate increased risk of preterm birth and small for gestational age [7].…”
Section: Introductionmentioning
confidence: 97%